2014
DOI: 10.1007/s10461-014-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

Rectal-Specific Microbicide Applicator: Evaluation and Comparison with a Vaginal Applicator Used Rectally

Abstract: An applicator designed for rectal delivery of microbicides was tested for acceptability by 95 young men who have sex with men, who self-administered 4mL of placebo gel prior to receptive anal intercourse over 90 days. Subsequently, 24 of the participants self-administered rectally 4mL of tenofovir or placebo gel over 7 days using a vaginal applicator, and compared both applicators on a Likert scale of 1–10, with 10 the highest rating. Participants reported high likelihood to use either applicator in the future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In prior studies, the gel applicator used in this study elicited criticism from users[22,23], especially in qualitative evaluations. In this study, which used only quantitative measures for applicator evaluation, participants were less critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior studies, the gel applicator used in this study elicited criticism from users[22,23], especially in qualitative evaluations. In this study, which used only quantitative measures for applicator evaluation, participants were less critical.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the acceptability of potential rectal microbicides is affected by product formulation (i.e., gel, suppository, or douche) [1217], attributed lubrication capacity of gels [18,19], anticipated product effectiveness [17,20,21], application method [19,22,23], packaging and portability of the product [22,24], dosing regimen (i.e., daily, before receptive anal intercourse (RAI), or before and after RAI) [16,17,24], side effects [21,24], type of partner with whom the rectal microbicide will be used [19,24,25], frequency of RAI [26], accessibility of product (i.e., prescription versus over-the-counter) [17,21], ease of use of the product [16], and product’s effect on sexual pleasure [13,15]. However, these findings stem from studies that were either hypothetical (participants expressed their opinions without actually using a product), placebo trials (the products used did not contain agents that could potentially have microbicide properties) or Phase 1 safety trials in small numbers of low-risk participants.…”
Section: Introductionmentioning
confidence: 99%
“…An important component of semisolid and liquid dosage forms is the applicator [46]. To deliver microbicide gels to the vagina, several applicators have been used.…”
Section: Design Considerations For On-demand Productsmentioning
confidence: 99%
“…Most participants (68%) disliked the applicator due to its tampon-like shape, sharp edges of the exposed tip, and rectal fullness attributed to the air released from the applicator [48]. To address these complaints, Carballo-Dieguez et al developed a rectal-specific applicator that incorporated the Fleet Comfort Tip ™ , which is commonly used for enema administration [46]. Unfortunately, in this study comparing this rectal applicator with a vaginal applicator, users (MSM) had no specific preference for either applicator.…”
Section: Design Considerations For On-demand Productsmentioning
confidence: 99%
“…Marks et al (2000) found that potential MSM users of a microbicide have “stringent standards,” that is, they expect high HIV prevention efficacy from any product they would consider using. In addition, there is evidence that distinct user populations react quite differently to potential product characteristics, suggesting that development of a single, ideal microbicide product may not be realistic (Carballo-Diéguez et al, 2008; 2014b; Giguere et al, 2012; Jones et al, 2008; Kinsler et al, 2010; Kinsler et al, 2012). …”
Section: Introductionmentioning
confidence: 99%